Defect Reduction in Automotive Seat Manufacturing: A Lean Six Sigma Approach - Wongtong, Bundit; Jatunitanon, Poom; Inseemeesak, Bundit; Ketmuang, Yodnapha (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2025)
This study investigates the issue of rear cushion wrinkling in a pickup truck seat production line using the Lean Six Sigma (LSS) methodology. By applying the DMAIC framework, we identified that excessive tension in the extruded listing ﬂeece caused deformation, particularly in curved seat sections. To resolve this problem, we redesigned the ﬂeece by incorporating rectangular slots (15 × 5 mm) spaced 80 mm apart. As a result, wrinkling defects were reduced by 60%, from 312 to 187 pieces, lowering the overall defect rate from 4.05% to 1.61% over six months. This exceeded our initial goal of reducing defects to less than 2.0%. Additionally, this improvement led to estimated cost savings of 852,500 THB, primarily due to a reduction in rework and material waste. Beyond cost benefits, the new design helped streamline the production process, cutting cycle time by 20% and improving customer satisfaction by a similar percentage. While these results demonstrate the eﬀectiveness of Lean Six Sigma in quality improvement, certain limitations remain. Factors such as operator variability and material inconsistencies were not fully controlled in this study. Future research could explore real-time defect detection systems or adaptive tension control mechanisms to enhance process stability.